2019
DOI: 10.1080/21691401.2018.1552594
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exposure of osteoblast-like cells to low-dose silver nanoparticles: uptake, retention and osteogenic activity

Abstract: Objective: Silver nanoparticles (AgNPs) are widely used in orthopaedic implants because of their excellent antimicrobial properties. However, the effects of AgNPs on bone cells and osteogenic activity are still poorly understood. Method: Here, we investigated the effect of AgNPs on the cell viability, uptake, and osteogenic activity of osteoblast-like cells (MG-63 cells) at low concentrations. Results: Our results showed that uptake and retention of AgNPs reduced the cell viability and increased cell membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 38 publications
(43 reference statements)
2
23
0
Order By: Relevance
“…On the one hand, as reported by Beck et al [ 37 ], small-sized mesoporous silicon particles may promote the proliferation of osteoblasts. On the other hand, the low concentration of silver nanoparticles packaged in the hall can also effectively promote short-term cell proliferation [ 15 ]. For hollow porous silicon, the pore diameter and hollow area are considered to be important parameters to improve drug loading capacity and dominate the release kinetics [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, as reported by Beck et al [ 37 ], small-sized mesoporous silicon particles may promote the proliferation of osteoblasts. On the other hand, the low concentration of silver nanoparticles packaged in the hall can also effectively promote short-term cell proliferation [ 15 ]. For hollow porous silicon, the pore diameter and hollow area are considered to be important parameters to improve drug loading capacity and dominate the release kinetics [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that 20~50 nm of silver nanoparticles with concentrations up to 2% can effectively inhibit microorganisms without causing obvious cytotoxicity [ 14 ]. Xie et al [ 15 ] found that due to the accumulation of intracellular Ag nanoparticles, their cytotoxicity often appears to be time-dependent after being cocultured for many days. Furthermore, studies have shown that silver nanoparticles have an effect on osteogenic activity [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the use of nanoparticles is very promising, but this is less known and controllable, and it has been not used as a strategy of the present research in order to avoid potential cytotoxicity concerns [8]. A low dose of silver might have a beneficial effect on the bone formation, as it could promote the proliferation and osteogenesis of the mesenchymal stem cells and have an inhibition effect on the production of the Tumor Necrosis Factor cytokine (TNF-α), resulting in an inhibition of osteoclastogenesis and inflammation [9,10]; however, a wrong concentration can also lead to an opposite effect, resulting in strong cytotoxicity and imbalance toward the osteoclasts formation, thus interfering with the bone remodeling process [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, in vitro experiments looking at the effects of long-term exposure are lacking in the AgNP toxicology literature. Most in vitro studies limit AgNP exposure to 24–72 h [25,32,37,38,39,40,41,42,43,44,45], with one report extending in vitro exposure to three weeks and reporting no toxicity from AgNP exposure to human corneal epithelial cells or murine eye-associated macrophages [62]. However, in this study, only one assay, which indirectly estimated cell death, was used to assess cytotoxicity from AgNP exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Particles become coated with macromolecules, such as proteins or growth factors, found in biological serum and the cell recognizes and engulfs these macromolecules, unknowingly also engulfing AgNPs. Numerous in vitro studies have shown that AgNPs can induce both cytotoxicity and genotoxicity in a variety of mammalian cells [25,32,37,38,39,40,41,42,43,44,45], as well as effects on differentiation state [46]. Specifically, there are reports of AgNP-dependent cell cycle arrest in G1 [47,48], S-phase [49,50], and at the G2/M transition [39,51].…”
Section: Introductionmentioning
confidence: 99%